The assessment of preparation of patients with chest drainage for self-care - Grochans, Elżbieta; Czekała, Irena; Kuczyńska, Magdalena; Szkup-Jabłońska, Małgorzata; Jurczak, Anna; Wieder-Huszla, Sylwia; Mroczek, Bożena; Gorzkowicz, Bożena; Karakiewicz, Beata (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2011)
Background: Preparation of patients for self-care activities gives both nurses and patients the feeling of self-fulfilment in their mutual relations. Aim of the study : The aim of this study was to assess preparation of patients with chest drainage for self-care. Material and methods: The study included 120 patients at the Clinical Ward of the VII Department of Chest Surgery, the Pomeranian Medical University in Szczecin. Inclusion criterium was the use of drainage of pleural cavity. The following instruments were used in this survey-based study: the Zubrod score and the author’s questionnaire including sociodemographic data, sources of information, and patients’ knowledge of self-care. Results : The majority of patients with chest drainage (69.2%) said that discharge from hospital with a drain would be a problem for them. Nurses were the most commonly mentioned source of information on the functioning of chest drainage (66.3%). The average test score was 5.2, and the maximum – 7. It was found that there was no correlation between the amount of information about the functioning of drainage and the test score (p > 0.05). The analysis demonstrated that patient anxiety about discharge from hospital with a drain did not depend on the level of activity according to Zubrod (p > 0.05) or the number of stays in hospital (p > 0.05). Conclusions : 1. The achieved level of preparation for self-care enabled patients with chest drainage to use a drain without any assistance. 2. Patients with chest drainage felt anxious about taking care of themselves at home and their anxiety did not depend on the level of their activity according to Zubrod or the number of stays in hospital. 3. There is a need for further studies on the causes of anxiety demonstrated by patients discharged from hospital with chest drainage. Key words: chest drainage, nursing, self-care.